Lower predicted probabilities of attained Lifés Simple 7 factors in the presence of sleep problems. (30th September 2020) - Felisbino-Mendes, M; Andrade, F; Dias Moreira, A; Hernandez, R; Vieira, M A; Velasquez-Melendez, G
Abstract: Background: Given that sleep disturbances seem to be increasing in Brazil, this may have serious implications on Cardiovascular Health and mortality. Objective: To examine the predicted probabilities of attained Lifés Simple 7 factors (LS7) in the presence of sleep problems among Brazilian adults. Methods: We used data from the 2013 Brazilian National Health Survey (PNS), a nationally representative cross-sectional household survey of adults in Brazil. Cardiovascular Health was assessed by the sum of Lifés Simple 7 factors (LS7), which includes four behaviors (smoking, physical activity, body mass index and diet) and three biological factors (hypercholesterolemia, hypertension and diabetes). We analyzed self-reported data from 36, 480 Brazilian adults aged 18 and over, including the sleep problems. We estimated predicted probabilities after multivariate Poisson regression. Results: Mean CVH scores was higher among those who did not report sleep disturbances [4.2 (95% CI: 4.1; 4.2)], than those with sleep disturbances [3.8 (95% CI: 3.7; 3.8)]. Predicted probabilities of attained LS7 and CVH score was lower in the presence of sleep complaints, with a dose response for blood pressure, glucose, smoking and CVH score in both unadjusted and adjusted analyses, for age, sex, schooling, depression and night work shift. Conclusions: Brazilian adults with sleep disturbances are less likely to achieve LS7 and consequently ideal cardiovascular health. Given that sleep disturbances seem to be increasingly more common in Brazil, recent gains in CVH mortality may be affected. Key messages: Sleep disturbances may potentially affect metabolic outcomes and modifiable lifestyles behaviors as decreased physical activity and smoking. Sleep disturbances is novel risk factor for metabolic diseases.